Rozwiąż równanie :
A) 0,2x+0,3=1,3
B) 5x-0,8=0,1+2x
C) 8x-0,2=8x-0,1
D) 0,01x +17=-0,16x
E) -0,07(10x-1)=0,3x
F) 0,83x + 0,82=0,23x+1,52
G)0,6x+2(0,1x-0,1)=0,2(x+1)
H) 0,7(x+2)=0,4(x+1)+0,3x+1
I) 0,15(2x+4)=2(1,3+0,3x)-0,6
J)0,1(x+1)-0,05(3x-10)=0,4-0,35x

2

Odpowiedzi

2010-03-18T18:13:32+01:00
A)
0,2x+0,3=1,3
0,2x=1,3-0,3
0,2x=1
x=5

B)
5x-0,8=0,1+2x
5x-2x=0,1+0,8
3x=0,9
x=0,3

C)
8x-0,2=8x-0,1
8x-8x=-0,1+0,2
0=0,1

D)
0,01x +17=-0,16x
0,01x+0,16x=-17
0,17x=-17
x=-100

E)
-0,07(10x-1)=0,3x
-0,7x+0,07=0,3x
-0,7x-0,3x=-0,07
-x=-0,07
x=0,07

F)
0,83x + 0,82=0,23x+1,52
0,83x-0,23x=1,52-0,82
0,6x=0,7
x=1⅙

G)
0,6x+2(0,1x-0,1)=0,2(x+1)
0,6x+0,2x-0,2=0,2x+0,2
0,6x+0,2x-0,2x=0,2+0,2
0,6x=0,4
x=⅔

H)
0,7(x+2)=0,4(x+1)+0,3x+1
0,7x+1,4=0,4x+0,4+0,3x+1
0,7x-0,4x-0,4x-0,3x=1-1,4
-0,4x=-0,4
x=1

I)
0,15(2x+4)=2(1,3+0,3x)-0,6
0,3x+0,6=2,6+0,6x-0,6
0,3x-0,6x=2,6-0,6-0,6
-0,3x=1,4
x=-4⅔

J)
0,1(x+1)-0,05(3x-10)=0,4-0,35x
0,1x+0,1-0,15x+0,5=0,4-0,35x
0,1x-0,15x+0,35x=0,4-0,1-0,5
0,3x=-0,2
x=-⅔
2010-03-18T18:28:47+01:00
A)0,2x + 0,3 = 1,3
0,2x = 1,3 - 0,3
0,2x = 1 |*5
x = 5
b)5x - 0,8 = 0,1 + 2x
5x - 2x = 0,1 + 0,8
3x = 0,9 |:3
x = 0,3
c)8x - 0,2 = 8x - 0,1
8x-8x=0,1+0,2
0=0,1 <-----sprzeczność
d)0,01x+17=-0,16x
0,01x+0,16x=-17
0,17x=-17 |*100
17x=-1700 |:17
x=-100
e)-0,07(10x-1)=0,3x
-0,7x-0,07=0,3x
-0,7x-0,3x=0,07
-x=0,07 |*(-1)
x=-0,07
f)0,08x+0,82=0,23+1,52
0,08x-0,23x=1,52-0,82
-0,15x=0,70 |*100
-15x=70 |:(-15)
x=4 2/3
g)0,6x+2(0,1x-0,1)=0,2(x+1)
0,6x+0,2x-0,2=0,2x+0,2
0,6x+0,2x-0,2x=0,2+0,2
0,6x=0,4 |*10
6x=4 |:6
x= 6/4
h)0,7(x+2)=0,4(x+1)+0,3x+1
0,7x+1,4=0,4x+0,4+0,3x+1
0,7x-0,4x-0,3x=0,4+1-1,4
0=0 <---- zdanie prawdziwe
i)0,15(2x+4)=2(1,3+0,3x)-0,6
0,3x+0,6=2,6+0,6x-0,6
0,3x-0,6x=2,6-0,6-0,6
0,3x=1,4 |*10
3x = 14
x= 4 2/3
j)0,1(x+1)-0,05(3x-10)=0,4-0,35x
0,1x+0,1-0,15x-0,5=0,4-0,35x
0,1x-0,15x+0,35x=0,1-0,5+0,4
0,3x=0 |*10
3x = 0 |:3
x=0